2003
DOI: 10.1099/ijs.0.02110-0
|View full text |Cite
|
Sign up to set email alerts
|

Eubacterium pyruvativorans sp. nov., a novel non-saccharolytic anaerobe from the rumen that ferments pyruvate and amino acids, forms caproate and utilizes acetate and propionate

Abstract: Two similar Gram-positive rods were isolated from 10 "6 dilutions of ruminal fluid from a sheep receiving a mixed grass hay/concentrate diet, using a medium containing pancreatic casein hydrolysate as sole source of carbon and energy. The isolates did not ferment sugars, but grew on pyruvate or trypticase, forming caproate as the main fermentation product and valerate to a lesser extent. Acetate and propionate were utilized. One of these strains, I-6 T , was selected for further study. Strain I-6 T was a non-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 26 publications
0
48
1
Order By: Relevance
“…Eubacterium pyruvativorans is one of several non-saccharolytic bacteria isolated from the sheep rumen on the basis that it was able to grow on trypticase as the sole source of energy as well as a N source (Eschenlauer et al, 2002). This species is fairly closely related to other non-saccharolytic bacteria isolated in the same study (Eschenlauer et al, 2002;Wallace et al, 2003) and in other studies of non-saccharolytic ruminal bacteria (Attwood et al, 1998), and to bacteria isolated from the oral cavity (Cheeseman et al, 1996;Wade et al, 1999a, b). The main fermentation products of E. pyruvativorans are caproate and valerate, with butyrate and propionatenormally end products of anaerobic fermentation in the rumen and elsewhere -apparently being utilized (Eschenlauer et al, 2002;Wallace et al, 2003).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Eubacterium pyruvativorans is one of several non-saccharolytic bacteria isolated from the sheep rumen on the basis that it was able to grow on trypticase as the sole source of energy as well as a N source (Eschenlauer et al, 2002). This species is fairly closely related to other non-saccharolytic bacteria isolated in the same study (Eschenlauer et al, 2002;Wallace et al, 2003) and in other studies of non-saccharolytic ruminal bacteria (Attwood et al, 1998), and to bacteria isolated from the oral cavity (Cheeseman et al, 1996;Wade et al, 1999a, b). The main fermentation products of E. pyruvativorans are caproate and valerate, with butyrate and propionatenormally end products of anaerobic fermentation in the rumen and elsewhere -apparently being utilized (Eschenlauer et al, 2002;Wallace et al, 2003).…”
Section: Introductionmentioning
confidence: 78%
“…pyruvativorans was named as such because it grew most rapidly on pyruvate (Wallace et al, 2003). Since pyruvate is not abundant extracellularly in the rumen (Wallace, 1978), it appeared that the true substrate for its growth in vivo was probably amino acids, although the net utilization of C 3 and C 4 volatile fatty acids (VFAs) and a slight utilization of lactate suggested that E. pyruvativorans might have a wider metabolic role.…”
Section: Introductionmentioning
confidence: 99%
“…The acetate production depends on PDH, which normally functions in aerobic metabolism (5,21,22). Eubacterium pyruvativorans is one of the few bacteria growing by fermentation of external pyruvate (35). The fermentation products are short-chain fatty acids, and the fermentation presumably requires PFOR.…”
Section: Resultsmentioning
confidence: 99%
“…Caproic acid is a side product in the acidogenic fermentation of a complex biomass or sugars (37,38). It is generally produced by anaerobic bacteria such as Clostridium kluyveri (39) and Eubacterium pyruvativorans (40) or by cocultures of C. kluyveri with ruminal cellulolytic bacteria using cellulose as a substrate (41). In this study, we observed significant correlations between caproic acid content and the relative abundances of four core prokaryotic populations (Lactobacillus, Clostridium IV [OTU2212], unclassified Clostridiaceae 1 [OTU3893], and unclassified Anaerobrancaceae [OTU3251]) (P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 99%